2009
DOI: 10.1120/jacmp.v10i3.2900
|View full text |Cite
|
Sign up to set email alerts
|

Application of a 3D volumetric display for radiation therapy treatment planning I: quality assurance procedures

Abstract: To design and implement a set of quality assurance tests for an innovative 3D volumetric display for radiation treatment planning applications. A genuine 3D display (Perspecta Spatial 3D, Actuality‐Systems Inc., Bedford, MA) has been integrated with the Pinnacle TPS (Philips Medical Systems, Madison WI), for treatment planning. The Perspecta 3D display renders a 25 cm diameter volume that is viewable from any side, floating within a translucent dome. In addition to displaying all 3D data exported from Pinnacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…purple is assigned to bone). Reproduced with kind permission of American Institute of Physics from Gong et al 11 …”
Section: Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…purple is assigned to bone). Reproduced with kind permission of American Institute of Physics from Gong et al 11 …”
Section: Treatment Planningmentioning
confidence: 99%
“…), however, with the Perspecta display, the planner only needs to move around the display to change their point of view. Quality assurance of the system was considered by Gong et al 11 Dose at sampled points were checked and found consistent with Pinnacle within 1% or 1 mm. The 3D spatial display of images, contours, and dose distributions exported from Pinnacle to Perspecta were consistent with Pinnacle display.…”
Section: An Immersive Vr Simulation Environment Rtstar (University Ofmentioning
confidence: 99%